Factors Influencing Assessment Literacy in Pre-Service Teachers: A Qualitative Study - Tavakolian, Shahrzad; Rahbarian, Behnam (Assessment and Practice in Educational Sciences, 2023)
This study aimed to explore the factors influencing the development of assessment literacy in pre-service teachers during their training programs in Tehran. Using a qualitative research design grounded in phenomenology, semi-structured interviews were conducted with 26 pre-service teachers enrolled in teacher education programs in Tehran. Participants were selected through purposive sampling to ensure diversity in gender, academic level, and subject specialization. Data collection continued until theoretical saturation was reached. Interviews were transcribed verbatim and analyzed using thematic content analysis with NVivo software. The coding process involved open, axial, and selective coding to extract categories and subcategories that reflected the participants’ experiences and perceptions. Analysis revealed four main categories: (1) conceptual understanding of assessment, (2) institutional and structural barriers, (3) attitudinal and emotional factors, and (4) professional identity and reflective growth. Participants demonstrated limited conceptual clarity about key assessment terms, showed overreliance on summative practices, and expressed confusion between feedback and evaluation. Structural challenges included inadequate practical training, limited curricular integration, and lack of mentoring. Emotionally, participants reported low self-efficacy, fear of mistakes, and passive learning habits. Nonetheless, signs of emerging reflective practice, ethical awareness, and a commitment to student-centered assessment were also evident. Assessment literacy in pre-service teachers is a multidimensional construct shaped by knowledge, beliefs, emotions, institutional conditions, and identity formation. The findings highlight a need for more integrated, practical, and reflective assessment training in teacher education programs. Supporting the development of assessment literacy requires systemic curriculum reforms, stronger practicum mentoring, and a shift toward formative, ethical, and learner-centered practices.